Increasing Social Care Through Civic Education in Higher Education - Suyato, Suyato; Hidayah, Yayuk (Jurnal Cakrawala Pendidikan, 2024)
This study aims to build social care through an engagement-based Civic Education curriculum at Universitas Negeri Yogyakarta/UNY whose students have diverse backgrounds. This study was developed based on the qualitative approach through 1) a focus group discussion to examine the engagement learning model in the Civic Education curriculum, 2) a workshop on the development of engagement learning models, 3) expert validation using the engagement learning model instrument, 4) implementation of engagement learning model, and 5) reflections on the engagement learning model implementation. The results of this study show that the Engagement Learning Model can improve social care shown from mutual respect for diversity, social cohesion, sympathy for others, and volunteerism. The researcher used the social value theory to analyze students’ social care. This engagement learning model can develop a social collaboration that promotes the unique characteristics of each student. Students are trained to be critical and socially sensitive through an engagement project consisting of social activities in the community in Civic Education learning. Increasing students’ care from Civic Education may positively influence students’ knowledge, attitudes, and social relations in their groups and outside their groups, respect and acceptance of diversity, social cohesion that forms cooperation, sympathy for others that form social solidarity, as well as a sense of volunteerism that makes students provide solutions to social problems.